2005
DOI: 10.1111/j.1365-3156.2005.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Falciparum malaria in the north of Laos: the occurrence and implications of the Plasmodium falciparum chloroquine resistance transporter (pfcrt) gene haplotype SVMNT

Abstract: Summaryobjective The Pfcrt-gene encodes a transmembrane protein located in the Plasmodium falciparum digestive vacuole. Chloroquine resistant (CQR) strains of African and Southeast Asian origin carry the Pfcrt-haplotype (c72-76) CVIET, whereas most South American and Papua New Guinean CQR stains carry the SVMNT haplotype.method Eighty-eight samples from an area with reported in vivo Chloroquine and in vitro Amodiaquine-resistance were screened for the K76T mutation and their Pfcrt-haplotype (c72-76) using a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
3
16
2
Order By: Relevance
“…This concurs with reports of the distribution of this gene in other geographic regions worldwide (1,17,18).…”
Section: Discussionsupporting
confidence: 81%
“…This concurs with reports of the distribution of this gene in other geographic regions worldwide (1,17,18).…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, in addition to the conventional in vivo and in vitro methods, the molecular markersbased approach to study and elucidate antimalarial drug resistance has proved useful [22][23][24][25][26]29,30,32]. In this study, we described the distribution of pfcrt K76T and pfmdr1 N86Y mutations in the study area and attempted to evaluate the correlation of these mutations with in vivo clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In areas that have low levels of complex and multiclonal malaria infections, the inbreeding of malaria parasites having mutant genotypes could spread the antimalarial drug resistance at an extraordinary rate [28]. The prevalence of the SVMNT haplotype in highly malaria-endemic study areas indicates the wide spread of chloroquineresistant P. falciparum, which might have evolved due to prolonged use of antimalarial amodiaquine in malaria chemotherapy [29][30][31]. Studies have shown that P. falciparum mutant pfcrt haplotypes have selective advantage in competitive mosquito infections by protecting immature gametocytes from chloroquine [32].…”
Section: Discussionmentioning
confidence: 99%
“…One likely influence is the history of AQ and CQ use in these regions and the consequent selective pressure for pfcrt and pfmdr1 polymorphisms of one type or another. Haplotypes of pfcrt-encoding polymorphisms similar to those of the pfcrt alleles in South America and PNG have been reported from East Timor, Indonesia, the Philippines, Laos, India, and Iran (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In many of these regions AQ was widely used in the 1940s (50) and early 1950s before the advent of CQR (Fig.…”
Section: G8mentioning
confidence: 99%